2019
DOI: 10.1371/journal.pone.0215223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing patterns on grassland biomass and soil environments in China: A meta-analysis

Abstract: Background Grazing has important influences on the structures and functions of grassland ecosystems, but the effects of grazing patterns on grassland biomass and soil environments in China remain unclear. Objective We employed a meta-analysis to identify the response of biomass and soil environments to different grazing patterns in China. Methods Peer-reviewed journal articles were searched using the Web of Science and China National Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
82
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 61 publications
23
82
3
3
Order By: Relevance
“…The vertical line means RR ++ = 0. HG, heavy grazing; LG, light grazing; MG, moderate grazing [Colour figure can be viewed at wileyonlinelibrary.com] (Figure 3), a finding that contradicts several earlier reports (Hao & He, 2019;Ren et al, 2018;Zhou et al, 2017). We believe that the difference is due to the fact that the present study also took into account the differences in grazing intensities, whereas many earlier studies had focused only on HG.…”
Section: Effects Of Grazing On Plant Biomass and Storage Of Soil Ccontrasting
confidence: 86%
“…The vertical line means RR ++ = 0. HG, heavy grazing; LG, light grazing; MG, moderate grazing [Colour figure can be viewed at wileyonlinelibrary.com] (Figure 3), a finding that contradicts several earlier reports (Hao & He, 2019;Ren et al, 2018;Zhou et al, 2017). We believe that the difference is due to the fact that the present study also took into account the differences in grazing intensities, whereas many earlier studies had focused only on HG.…”
Section: Effects Of Grazing On Plant Biomass and Storage Of Soil Ccontrasting
confidence: 86%
“…Compared to previous meta-analyses that were limited by region or number of analyzed soil properties [11,12,19,[55][56][57][58], this study provides more insight into global grazing impacts on the soil by combining large-scale data of 15 soil properties.…”
Section: Meanmentioning
confidence: 99%
“…Recent meta-studies have shown that increasing grazing intensities in China generally have a negative impact not only on above—but also on belowground plant biomass 22 , 23 . This can lead to a reduction in plant C allocation and root excretion patterns, having a negative effect on microbial biomass and activity 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, grazing can change the spatial distribution of resources available for soil microorganisms by returning plant biomass in the form of feces and urine to soil 21 , 24 . Depending on stocking densities, the deposition of excrements thereby leads to a heterogeneous concentration of labile carbon and nutrients in the topsoil (0–10 cm) stimulating the soil microbial biomass and its activity at local spots 23 , 27 .…”
Section: Introductionmentioning
confidence: 99%